An analogy between effects of ultra-low doses of biologically active substances on biological objects and properties of spin supercurrents in superfluid 3He-B - Boldyreva, Liudmila B. (Homeopathy, 2011)
The effects of ultra-low doses (ULDs) of biologically active substances (BASs) (with concentrations of 10−13 M or lower) on biological objects (BOs), such as cells, organisms, etc., and the properties of spin supercurrents in superfluid 3He-B are discussed. It is shown that the effects of ULDs of BASs on biologic objects can be specified by the same set of physical characteristics and described by the same mathematical relations as those used for the specification and description of the properties of spin supercurrents between spin structures in superfluid 3He-B. This is based on the up-to-date physical concepts: 1) the physical vacuum has the properties of superfluid 3He-B; 2) all quantum entities (hence, the BAS and the BO, which consist of such entities) produce spin structures in the physical vacuum. The photon being a quantum entity, the features of the effects of low-intensity electromagnetic radiation on BOs can be explained using the same approach.
Keywords: Ultra-low doses; Low-intensity electromagnetic radiation; Homeopathy; Model of the superfluid physical vacuum; Spin supercurrents; Homogeneously precessing domain